Association between Petal Form Variation and CYC2-like Genotype in a Hybrid Line of Sinningia speciosa - Hsu, Hao-Chun; Wang, Chun-Neng; Liang, Chia-Hao; Wang, Cheng-Chun; Kuo, Yan-Fu (Frontiers in Plant Science, 2017)
This study used three-dimensional (3D) micro-computed tomography (μCT) imaging to examine petal form variation in a hybrid cross of Sinningia speciosa between a cultivar with actinomorphic flowers and a variety with zygomorphic flowers. The major objectives were to determine the genotype–phenotype associations between the petal form variation and CYCLOIDEA2-like alleles in S. speciosa (SsCYC) and to morphologically investigate the differences in petal types between actinomorphic and zygomorphic flowers. In this study, μCT was used to accurately acquire 3D floral images. Landmark-based geometric morphometrics (GM) was applied to evaluate the major form variations of the petals. Nine morphological traits of the petals were defined according to the form variations quantified through the GM analysis. The results indicated that the outward curvature of dorsal petals, midrib asymmetry of lateral petals, and the dilation of ventral region of the tube were closely associated with the SsCYC genotype. Multiple analyses of form similarity between the petals suggested that the dorsal and ventral petals of actinomorphic plants resembled the ventral petals of zygomorphic plants. This observation indicated that the transition from zygomorphic to actinomorphic flowers in S. speciosa might be caused by the ventralization of the dorsal petals. We demonstrated that the 3D-GM approach can be used to determine genotype–phenotype associations and to provide morphological evidence for the transition of petal types between actinomorphic and zygomorphic flowers in S. speciosa.